Time to pregnancy and infertility among women with a high intake of fish contaminated with persistent organochlorine compounds - Axmon, Anna; Rylander, Lars; Strömberg, Ulf; Hagmar, Lars (Scandinavian Journal of Work, Environment & Health, 2000)
' ' OBJECTIVES ': 'The purpose of this study was to assess the effect of persistent organochlorine compounds through the dietary intake of fatty fish from the Baltic Sea on human fertility.' ' METHODS ': 'Information on time to pregnancy, subfertility, and infertility was collected retrospectively by self-administered questionnaires in 2 cohorts of fishermen's wives from the Swedish east (by the Baltic Sea) and west coasts. In addition to cohort affiliation, current fish consumption and growing up in a fishing village were used as proxies for exposure within the eastcoast cohort.' ' RESULTS ': 'A decreased success (ie, pregnancy) rate and a tendency towards increased subfertility was found for heavy smokers (?10 cigarettes/day) in the eastcoast cohort as compared with the westcoast cohort [success rate ratio 0.66, 95% confidence interval (95% CI) 0.49-0.89; subfertility odds ratio 1.64, 95% CI 0.91-2.91). However, internal analyses within the eastcoast cohort did not show that growing up in a fishing village or high current fish consumption decreased the success rate. Eastcoast cohort affiliation showed an increased risk for infertility (odds ratio 2.49, 95% CI 1.05-5.92).' ' CONCLUSION ': 'The present data give some support for a negative association between exposure to persistent organochlorine compounds and fertility among heavy smokers. However, when the proxy exposure measures are also considered, the findings are not consistent. Better individual exposure assessments should be used before more firm conclusions are drawn.
Keywords: contamination; fertility; fish; infertility; PCP; persistent organochlorine compound; polychlorinated biphenyl; polychlorinated dibenzo-p-dioxin; polychlorinated dibenzofuran; time to pregnancy; woman